The role of local history in primary education: Learning through didactic itineraries - de León Perera, Cristo José (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
In the following pages we present the result of a didactic proposal implemented in the Degree in Teacher in Primary Education of the University School of Teaching of Zamora (University of Salamanca). An interdisciplinary didactic sequence was carried out, based on guided learning and cooperative work thanks to the resource of the didactic itinerary. Following what was proposed by Vygotsky and Bruner, we have aspired to the development of spontaneous and everyday learning through the use of the close environment of teachers and students -as well as their historical past-, favoring the acquisition of critical and individual thinking.